Pengaruh Dewan Komisaris Independen, Financial Distress, Dan Opini Audit Terhadap Auditor Switching (Studi Empiris Pada Perusahaan Sektor Financial Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022) - Siska Puspitasari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
This research aims to analyze the influence of the Independent Board of Commissioners, Financial Distress, and Audit Opinion on Auditor Switching (Empirical Study of Financial Sector Companies Listed on the Indonesian Stock Exchange in 2019-2022). The theory used in this research is agency theory. This research is included in quantitative research. The data used in this research comes from secondary data in the form of annual financial reports and audited financial reports from financial sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2022. The purposive sampling method was used to obtain the right sample for this research. A total of 87 companies known to meet the criteria were used as samples. And 348 company data was obtained for observation. The dependent variables in this research are Auditor Switching (AS) with the Independent Board of Commissioners (DKI), Financial Distress (FD), and Audit Opinion (OA). Tests were carried out on the data and then analyzed using the classic assumption test and multiple regression analysis using the SPSS 25 application. The results of the research showed that the Independent Board of Commissioners, Financial Distress and Audit Opinion variables had a positive effect on Auditor Switching.